EXAMINATION OF WORK ALIENATION IN EMPLOYEES IN TERMS OF SOME DEMOGRAPHIC VARIABLES (Third Sector Social Economic Review, 2018)
In this era, where informational and technological developments are rapidly increasing, it is very difficult fort he employees to exist with their productivity together with this technology. Many technological inventions brought about by industrialization have accelerated production, but have led to fewer employees and to the demand for less labor. These developments brought about the discussion of the concept of “labor” which is the biggest indicator of human existence and alienation of human labor. The aim of this study is to examine the concept of alienation and to examine the effects of demographic characteristics of the workers on alienation phenomenon. For this purpose, a questionnaire was applied to 435 personnel working in the governorship of Kırıkkale and public institutions affiliated to the governorship. In the applied questionnaire, the questionnaire which was developed by the researcher and questions containing demographic information were used. ANOVA, t-test, frequency analysis were used and the they data gathered were analyzed in the SPSS 16.0 program. As a result of the research, the researcher found out, some significant differences between the gender, marital status, working time and alienation of the workers.
Keywords: Employee; Demographic characteristics; Work Alienation